ANALISIS PENDAPATAN USAHA PETERNAKAN AYAM BURAS PEDAGING DI DESA BUNGUNGLOE KECAMATAN TURATEA KABUPATEN JENEPONTO - Tanri Giling Rasyid; Sofyan Nurdin Kasim (State Islamic University (UIN) Alauddin, 2014)
ABSTRACT. This study was carried out considering the free-range chicken farmers who undertake the cultivation, have different backgrounds in terms of the number of free-range chicken, the farmers’ experience, education and venture capital as well as the knowledge of the qualification of free-range chicken to be raised which at last will impact the increased revenue for the farmers. Due to those different backgrounds, the purpose of this study was to determine the feasibility of the business, and the income contribution of thedomestic poultry against the farmers. In order to answer the eligibility and income provided by the domestic poultry broiler flocks, the approach used is through an interview method to 20 respondents which is the primary data. Data based on the interview from 20 respondents, is then analysed using analysis model Pd = TR - TC and analysis used eligibility formula Revinue Per COSH (R/C). Based on the research analysis, it can be concluded that raising free-range chicken as many as 100, 300, 500 and 1000 will provide income for the farmers. The most efficient and effective way is by raising 300 free-range chicken according to the feasibility study with R / C = 1.51. Therefore, the result of this study is able to be recommended to those who has the intention to breed the free-range chicken, particularly to the domestic poultry broiler breeders in Bungungloe Village, Turatea District, Jeneponto Regency, South Sulawesi.